West End Girls - Colgan, Jenny (London Sphere, 2007)
They may be twin sisters, but Lizzie and Penny Berry are complete opposites - Penny is blonde, thin and outrageous; Lizzies is quiet, thoughtful and definitely not thin. The one trait they do share is a desire to do something with their lives, and as far as they are concerned the place to get noticed is London.
Keywords: Twins